A rare case of concurrent multichamber thrombosis complicated by cardioembolic stroke in a reversible postpartum thyrotoxic cardiomyopathy. (7th March 2013) - Parisi, Cristian; Canali, Emanuele; Proietti, Fabrizio
Abstract : We describe a rare case of cardiac multichamber thrombosis in a young woman admitted with heart failure and atrial fibrillation, who was later found to have reversible postpartum thyrotoxic cardiomyopathy. A transoesophageal echocardiogram demonstrated a patent foramen ovalis with an over-riding thrombus. The clinical scenario was complicated by a cardioembolic stroke upon spontaneous restoration of sinus rhythm.